Spirit Dakwah Ki Ageng Makukuhan dalam Spiritualitas Petani Tembakau Srinthil - Ahmad Hidayatullah; Ambar Hermawan (Fakultas Dakwah dan Ilmu Komunikasi, 2026)
Tobacco and the Temanggung community seem to have a bond between the two. Especially with the srinthil tobacco type, this variety really has a special place in the hearts of the Temanggung people, especially farmers. It is not just a plant that is treated as a mere commodity. More than that, there is a spiritual dimension to the farmers who grow srinthil tobacco. Using a type of qualitative research that is field research, as well as a phenomenological approach, the author tries to explore the phenomenon of spirituality of Srinthil tobacco farmers in Temanggung. The results of this research can be concluded that the manifestation of spirituality of srhintil tobacco farmers in the nyecel, nglekasi and miwiti traditions is found in the concept of tawakkal which places effort and prayer in proportion. The point of differentiation lies in the form of rites which are not formally taught in the primary sources of Islamic teachings (the Al-Qurán and Hadith). And this is part of the long history of da'wah carried out by Ki Ageng Makukuhan in that region. Although after being explored substantively, what happens in the nyecel, nglekasi and miwiti traditions is more in line with rather than contrary to the source of these teachings. Most people think that srinthil is a kind of